Development and Empirical Evaluation of a Gamification-Driven Learning Model for Digital Native Learners in Higher Education: The CIRCUS Framework - Nursetyo, Kunto Imbar; Situmorang, Robinson; Kusumawardani, Dwi (Universitas Islam Negeri Raden Intan Lampung, 2026)
This study aimed to develop and empirically evaluate a gamification-driven learning model designed to address the learning characteristics of digital native students in higher education. Despite the growing body of evidence supporting gamification as a pedagogical strategy, most implementations remain fragmented and lack a structured instructional design framework, representing a critical gap in the literature. This research employed a Research and Development (R&D) approach to design and validate an instructional model called CIRCUS, comprising six systematic stages: Consider Needs, Inspect Content, Regulate Objective, Construct Prototype, Utilize Prototype, and Summing-Up. The study involved three panels of participants: three Educational Technology experts who evaluated model validity, eighteen university lecturers who assessed model practicality, and 62 undergraduate students from Universitas Negeri Jakarta who participated in a field trial across Big Data and Programming courses. Validity was assessed using Aiken's V index, yielding an average of 0.87, which exceeds the minimum threshold of 0.80 and confirms strong expert agreement on the model's syntactic and conceptual coherence. Practicality was assessed through a 5-point Likert scale survey, with lecturers awarding an average score of 85%, categorized as very practical. The gamification product integrated into the Learning Management System was validated as feasible by content and media experts. The field trial demonstrated a statistically meaningful improvement in student learning achievement, increasing from a mean of 68% prior to implementation to 82% following the intervention, yielding a normalized gain of 0.44 (medium category). Furthermore, 89% of students earned all five available achievement badges and 94% completed the instructional game embedded in the system. These findings suggest that a structured, theoretically grounded gamification framework can meaningfully enhance engagement, participation, and academic performance among digital native learners. The CIRCUS model represents a replicable instructional design contribution that integrates gamification principles with established pedagogical objectives.